Iberian Market Integration: A Case Study of a Regional Integration Process - Iva Miranda Pires (European Regional Science Association (ERSA), 2006)
In spite of being neighbors the economic relations between Portugal and Spain where irrelevant until recently. Each one of the countries chose, after 2nd War World, different options (Spain's internal market permitted import-substitution, while Portugal's smaller scale and 'special relationship' with the UK encouraged greater openness) and some aspects of the common history (Spain invaded and stayed in Portugal during almost one century) created some distrust reinforced by the unequal dimension of the neighboring country. But Portuguese and Spanish jointly adhesion to EEC, in 1986, created a totally new context that would come to facilitate and even to stimulate the development of the relationships inside Iberian Peninsula. This two until recently quite independent territories are been (re) shaped by intensive economic (and to a less extent social) interdependencies. Another aspect relates with the dynamism of the integration process if we look at the booming of trade and FDI flows between the two economies. Among the main driving forces of the Iberian market integration we identify EU itself deepening process of integration (common market, common economic, social and environment policies, abolition of borders); national governments (namely developing transport and communication infrastructures that facilitate regional mobility) and the economic agents that fast adapt to the new enlarged market exploring opportunities in each of the neighbouring markets. Empirical data on EU process of integration and accomplishment of internal market shows that countries that belong to EU tend to rely more and more on other EU members as a partner to develop trade and FDI flows. After EU adhesion Spain and Portugal quickly become relevant economic partners although due to a more active reaction of Spanish capitals the process has not been consensual in Portugal; complains on the so called "invasion" from Spanish investments where common in the media. More pro-active arguments support that although pursuing a friendly neighbouring relation with Spain Portugal should, at the same time, diversify its internationalisation strategy. The aim of this paper is to assess the impact of Spanish investment in Portugal and Portuguese firms' adaptation to new Iberian market opportunities and challenges.
Keywords: 330